Climate change and economic growth: Some critical reflections - Alfred Greiner (Bielefeld University, Faculty of Business Administration and Economics, 2022)
Empirical studies analyzing the effect of climate change on output growth sometimes neglect economic variables. This yields a biased picture of the growth process and does not represent a good approximation of the true data generating process. Thus, the question arises how valid the results are so that analyses investigating the robustness of the outcome with respect to integrating economic variables should be carried out.
urn:nbn:de:0070-pub-29606452
Keywords: 330; Climate change; Economic growth; Klimawandel; Wirtschaftswachstum; Theorie